Deteksi Korosi Pipa Menggunakan Sinyal Suara - Ariya Sujatmiko; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The piping systems are an important part of infrastructure in industry, such as the gas and oil industry as a transport in circuits of liquids and gases from one point to another. Problems often found in piping systems are corrosion, leaks, and blockages. Corrosion is the beginning of leakage and blockage. Corrosion detection method in developed pipe, for example radiography method that utilize electromagnetic wave, while method of ultrasonic testing is utilize ultrasonic wave. The disadvantages of both methods are high cost and difficult to operate. The purpose of this research is to analyze sound signal at corrosion pipe by giving acoustic excitation and Identify the change of sound signal that happened due to corrosion position on surface in pipe. In this paper, the basis of corrosion detection in pipes is reflectometry waves using acoustic methods. Reflectometry waves are reflected waves that propagate in the diameter of the pipe. If there is a difference in diameter in the pipe then some waves will be continued along the pipe and the other waves will bounce towards the sound source . Stages of data retrieval is done when filled with air pressure 1 atm and air with various types of corrosion. The way data is collected by giving the sound excitation, then the signal is processed by transfomenting to the form of fast fourier transform and wavelet transform. The result of examination was obtained emission of acoustic that got detection of corrosion position on pipe diameter and also got estimation error under 10 %.Keyword : Piping System, Corrosion, Reflectometry, Sound Signal, Fast Fourier Transformation, Wavelet